Effect of melt/mantle interactions on MORB chemistry at the easternmost Southwest Indian Ridge (61°–67°E). (21st November 2016) - Paquet, M.; Cannat, M.; Brunelli, D.; Hamelin, C.; Humler, E.
Abstract: The easternmost part of the Southwest Indian Ridge (61°–67°E) is an end‐member of the global ridge system in terms of very low magma supply. As such, it is a good laboratory to investigate the effect of melt/mantle interactions on the composition of erupted basalts: for a given volume of erupted basaltic melt, the volume of reacted mantle is potentially greater than at more magmatically robust ridges. We analyzed major, trace element and isotopic compositions in three groups of rocks: plagioclase‐bearing ultramafic and gabbroic rocks dredged in nearly amagmatic spreading corridors; basalts from the sparse volcanic cover of these corridors ("ultramafic seafloor basalts"); and basalts dredged from the intervening, more volcanically active domains ("volcanic seafloor basalts"). Ultramafic seafloor basalts have significantly lower CaO and Al2 O3 contents at a given MgO than most volcanic seafloor basalts. We propose that both types of basalts are derived from similar parental melts, but that the ultramafic seafloor basalts are more affected by reactions between these parent melts and the mantle rocks in the lithosphere below the ridge. We infer that these reactions occur in the walls of conduits that allow the aggregated melts extracted from the melting mantle to rise through the axial lithosphere and to the eruption sites. The principal effect of these reactions is to enrich the asthenospheric melts in MgO through olivine dissolution. This effect is not expected to be as noticeable, but could still play a role in basalt petrogenesis at more magmatic regions of the global slow‐spreading MOR system. Key Points: At the easternmost SWIR, ultramafic seafloor basalts have lower CaO and Al2 O3 contents at a given MgO than most volcanic seafloor basalts Both types of basalts are derived from similar parental melts, but ultramafic seafloor basalts are more affected by melt‐mantle reactions The principal effect of these reactions is to enrich the asthenospheric melts in MgO through olivine dissolution